IMPLEMENTASI REGRESI PANEL DALAM ANALISIS PENGARUH PARTISIPASI WANITA DI INDONESIA TERHADAP PENGANGGURAN PASCA PANDEMI COVID-19 - Dani Rahmad Setiawan (Jurnal Bayesian : Jurnal Ilmiah Statistika dan Ekonometrika, 2024)
The role of women is vital for the implementation of equitable and sustainable development. Especially in the post-Covid-19 pandemic period, many socio-cultural structural changes have occurred. This study aims to analyze the influence of women's labor force participation and the Human Development Index (HDI) on open unemployment rates in Indonesia. This study utilizes quantitative and secondary data of 34 provincies in the period 2020-2022 from the Indonesian Central Statistics Agency and examines the relationships between variables using panel data regression analysis. It finds that that Human Development Index for women has a significant negative impact on open unemployment rates, while the impact of women's labor force participation on is not. A comprehensive policy regarding increasing the women's human development index is needed which can have the effect of reducing the level of open unemployment in Indonesia. This study contributes to understanding the complex dynamics of labor force participation, human development, and unemployment in Indonesia, providing valuable insights for policymakers and researchers